1999
DOI: 10.1074/jbc.274.44.31663
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Conformational Modifications of Wild-type p53 and Suppresses p53 Response to DNA Damage in Cultured Cells

Abstract: The p53 tumor suppressor protein is a transcription factor that binds DNA in a sequence-specific manner through a protein domain stabilized by the coordination of zinc within a tetrahedral cluster of three cysteine residues and one histidine residue. We show that cadmium, a metal that binds thiols with high affinity and substitutes for zinc in the cysteinyl clusters of many proteins, inhibits the binding of recombinant, purified murine p53 to DNA. In human breast cancer MCF7 cells (expressing wild-type p53), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(114 citation statements)
references
References 55 publications
(59 reference statements)
8
102
0
1
Order By: Relevance
“…p53 initiates apoptosis during high levels of stress (Schwartz and Rotter, 1998), and MT has been shown to play a role in different aspects of apoptosis. Further evidence is provided by a recent study showing that cadmium can affect the stability and DNAbinding activity of p53 (Méplan et al, 1999). In MCF7 cells, 10 mM of CdCl 2 caused an increase in p53 protein level and DNA binding activity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…p53 initiates apoptosis during high levels of stress (Schwartz and Rotter, 1998), and MT has been shown to play a role in different aspects of apoptosis. Further evidence is provided by a recent study showing that cadmium can affect the stability and DNAbinding activity of p53 (Méplan et al, 1999). In MCF7 cells, 10 mM of CdCl 2 caused an increase in p53 protein level and DNA binding activity.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, MT may have antioxidant properties because of its high cysteine content which may protect against DNA damage (Cai et al, 1996). A recent study has shown that treatment of MCF7 cells with 10 mM CdCl 2 can increase MT-IIA isoform and can protect against cadmium toxicity (Méplan et al, 1999). Since MCF7 cells were much more sensitive to cadmium toxicity as compared to HCC1806 and MDA-MB-231, a higher induction of MT in MCF7 cells may be required to protect against cytotoxicity and DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is known that p53 has a metal-binding feature and is inactivated by exposure to cadmium ions. 24,33 Accordingly, we propose that the metal-binding site in p53 may be targeted by the vanadate anion(s).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to pursue other possibilities, we examined the effects of vanadate on the conformation of p53 using the anti-p53 PAb 240 mAb as a probe for the inactivated form of p53. [22][23][24] In nondenaturing conditions, PAb 240 mAb recognizes the inactivated form of p53 but not the normal form, whereas the DO-1 mAb recognizes both forms. PAb 240 mAb immunoprecipitated the p53 from irradiated MOLT-4 cells treated with vanadate but not from cells exposed to X-rays alone ( Figure 8a).…”
Section: Vanadate Suppresses P53-dependent Dna Damage-induced Apoptosismentioning
confidence: 99%
“…Experimental studies suggest several pathways to explain association of Cd with human breast cancer [8,10,11]. There is evidence that Cd may have estrogenicity [8,12,13].…”
Section: Introductionmentioning
confidence: 99%